Chapter Combinatory Categorial Grammar - Steedman, Mark (Comparative Handbooks of Linguistics [CHL], 2019)
In this handbook thirteen current approaches to syntactic description are presented (Part I) along with six studies on their metatheoretical underpinnings (Part II). The goal is to facilitate a systematic comparison among the approaches. All accounts address the same issues and are structured uniformly for an item-by-item survey across the frameworks. The volume is of interest for grammarians, philosophers of science, and cognitive scientists.